Development of Contemporary Home Decorative Textiles Based on Gesek Godhong Technique and Gorontalo Floral Motifs - Ulin Naini; Hasmah Hasmah (LPPM Institut Seni Indonesia Padangpanjang, 2026)
The development of contemporary interior design has increased the demand for home decorative textile products that are not only functional but also aesthetically valuable, locally distinctive, and environmentally sustainable. This study aims to develop contemporary home decorative textiles based on the gesek godhong technique by utilizing Gorontalo floral motifs as visual sources. The research employed an artistic experimental method with a descriptive-qualitative approach. Data were collected through observation, literature study, interviews, and studio experiments, and were then processed through the stages of material exploration, motif design, artwork realization, and visual evaluation. The results show that the gesek godhong technique is capable of producing distinctive floral motifs through the transfer of leaf shapes, textures, and structures onto fabric surfaces. The realized products, including cushion covers, tablecloths, and curtains, demonstrate strong visual qualities through the arrangement of lines, colors, rhythm, balance, and motif composition. The use of leaves as motif sources and the color fixation process creates unique visual characteristics while supporting the development of decorative textiles with artistic, economic, and ecological value. This study confirms that the gesek godhong technique can serve as an innovative alternative for developing contemporary decorative textile designs based on Gorontalo’s local potential